Unpacking provisions related to transparency of mitigation and support in the Paris Agreement - Briner, Gregory (OECD/IEA Climate Change Expert Group Papers, 2016)
The agreement of an enhanced transparency framework was a key outcome of the COP 21 climate change conference in Paris. This enhanced transparency framework will play an important role in tracking progress towards the individual and collective goals agreed at COP 21 and in understanding achievement of nationally determined contributions under the Paris Agreement. This paper unpacks the transparency-related provisions within the Paris Agreement and Decision 1/CP.21 relating to mitigation and support. It also explores the relationship between the existing and future transparency framework, information required to track progress towards nationally determined contributions for mitigation, and fulfilling reporting provisions on finance provided, mobilised and received